THE EFFECTIVENESS OF TEACHING READING DESCRIPTIVE TEXT BY USING COOPERATIVE LEARNING STRATEGY OF SMAN 4 KEDIRI - Kusniawati, Mei (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 9 No 1 (2019): LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
This study aims at knowing how the Cooperative Learning strategy affects the reading ability of the first grade students at SMAN 4 Kediri in comprehending descriptive text.The research design which is used in this research was descriptivequantitative experimental with one group pre-test and post-test design.  The subjects of this research were students from X-8. The instruments used were pre-test and post-test. The data gotten were statistically computed by SPSS. The result of this study showed that t-test is 17,881. Itâ€™s higher than t.table at either 5% or 1% significancy level.So, it can be concluded that teaching reading descriptive text by using Cooperative Learning strategy is effective.